Anti-hypertensive effect of a novel angiotensin II receptor neprilysin inhibitor (ARNi) -S086 in DSS rat model - Sun, Jingchao; Xiao, Ying; Xu, Wenjie; Xing, Wei; Du, Frank; Tian, Maozhi; Xu, Danqi; Ren, Yihua; Fang, Xin (Frontiers in Cardiovascular Medicine, 2024)
Introduction Angiotensin receptor-neprilysin inhibitor (ARNi), comprised of an angiotensin receptor blocker (ARB) and a neprilysin inhibitor (NEPi), has established itself as a safe and effective intervention for hypertension. S086 is a novel ARNi cocrystal developed by Salubris for the treatment of heart failure and hypertension. Methods Dahl Salt Sensitive (DSS) hypertensive rat model and telemetry system were employed in this study to investigate the anti-hypertensive efficacy of S086 and compare it with the first ARNi-LCZ696. Results and discussion The study showed that oral administration of S086 dose-dependently lowered blood pressure (P < 0.001). The middle dosage of S086 (23 mg/kg) exhibited efficacy comparable to LCZ696 (68 mg/kg), while also demonstrating superiority at specific time points (P < 0.05). Notably, water consumption slightly decreased post-treatment compared to the vehicle group. Furthermore, there were significant increases in natriuresis and diuresis observed on the first day of treatment with 23 mg/kg and 68 mg/kg S086 (P < 0.001). However, over the course of treatment, the effects in all treatment groups gradually diminished. This study demonstrates the anti-hypertensive efficacy of S086 in DSS hypertensive rat model, offering promising avenues for the clinical development of S086 as a hypertension treatment.